Type of Childbirth and its Association with the Maternal-Filial Interaction - Crystiane Hereny dos Santos Neto; Fábio Sagula Oliveira; Graciele Fernanda Gomes; Edward Araujo Júnior; Mary Uchiyama Nakamura; Eduardo de Souza (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2020)
Abstract Objective The purpose of the present study was to evaluate the quality of mother-child bonding in three different contexts related to the labor, that is, vaginal delivery, elective cesarean section, and intrapartum cesarean section. Methods This was an observational, cross-sectional clinical study conducted in two cities within the state of São Paulo, Brazil. The study sample consisted of 81 babies born without any major complications during pregnancy and labor, aged 3 to 4 months, and their respective mothers, aged between 20 and 35 years old, primiparous, living in the cities of Palmital and Ourinhos, state of São Paulo, Brazil. The evaluation of the quality of the maternal-filial interaction was performed through video-image analysis, using the Mother-baby Interaction Observation Protocol from 0 to 6 months (POIMB 0-6, in the Portuguese acronym). Results Mothers who had vaginal delivery had higher amount of visual contact or attempted visual contact (p = 0.034), better response to the social behavior of the child (p = 0.001) and greater sensitivity (p = 0.007) than the others. Their children also showed more interaction with them, as they looked more frequently at the mother's face (p ≤ 0.008) and responded more frequently to the mother's communicative stimulus (p < 0.001). Conclusion Considering the occurrence of vaginal delivery, it is concluded that the interaction between the mother-child dyad is quantitatively larger and qualitatively better when compared with intrapartum or elective cesarean section.